Associations between the Falls Efficacy Scale International (FES-I) and poor strength and balance in community-dwelling older people - Lewis McColl; Victoria Strassheim; Matthew Linsley; David Green; Charlotte Dunkel; Heidi Trundle; Jake R Gibbon; Steve W Parry (Cogent Gerontology)
Concern about falling (CaF) is associated with higher falls risk in community-dwelling older adults. Our aim was to determine whether CaF (as measured by the Falls Efficacy Scale International version (FES-I)) is associated with poor functional mobility and balance in older adults. Sensitivity and specificity analysis was carried out to test for associations. FES-I score had good to excellent sensitivity when predicting timed up and go (TUG) (87.1%), five times sit to stand time (FTSS) (82.9%) and gait speed (GS) (81.4%) indicative of poor mobility and balance. Moderate specificity was also observed when predicting GS (55.2%) and FTSS (62.3%); a low-to-moderate specificity was observed when predicting TUG (50.0%). A FES-I score indicating CaF showed high specificity and moderate specificity in identifying those with poor scoring. Further work is needed to prospectively assess the relationship between the FES-I and poor mobility and balance.